Performance & Emission Characteristic Of Emulsified Biofuel Application In Diesel Engine - Hamid, Mohd Fadzli (2017)
The depletion of fossil fuel reserve and the fluctuation of oil prices in the global market have triggered global awareness and interest in developing alternative fuels. Fossil fuel has become a major environment concern due to its detrimental pollution effect. Crude palm oil (CPO) is one of the most potential biofuels that can be applied in the conventional diesel engines, since its chemical properties are comparable to that of diesel fuel. However, its higher viscosity and heavier molecules can contribute to several engine problems such as low atomization during injection, carbon deposit formation and injector clogging. An emulsification of biofuel and modifications of few engine critical components that include the incorporation of Guide Vane at the inlet manifold and the search for new piston bowl design have been identified as a promising solutions to mitigate the issues. This study presents the results of both numerical and experimental investigations showing the effects of dissimilar guide vane design (GVD) in terms of height variation of 0.25R, 0.3R and 0.35R at the intake manifold and dissimilar piston bowl designs with respect to OCB, OCC and SCC to the in-cylinder air flow characteristics improvement. The GVD designs and Piston modifications have been fabricated and tested to the Yanmar L70AE engine. The GVD designs and Piston modifications have been modelled using SOLIDWORK 2014, and ANSYS FLUENT 15 is employed and utilized to run a three dimensional (3D) cold flow internal combustion (IC) engine simulation. Both simulation and experimental results show that the intake manifold with GVD improved the performance of the air flow characteristic particularly swirl, tumble and cross tumble ratios from the intake manifold to the engine. The GVD with the height of 0.3R was found to be the optimum design with respect to the overall improvement of the air flow characteristic. The improvement of the air flow characteristics with the application of GVD and SCC piston in the engine was proven to be successfully contribute to a better air fuel mixing and fuel atomization as based on the results of engine performance characteristics improvement throughout the experiment.